Analisis Faktor-Faktor Yang Mempengaruhi Produksi Jagung Di Kabupaten Aceh Tenggara - Yusuf, Husainah; Hasnudi, Hasnudi; Lubis, Yusniar (JURNAL AGRICA, 2014)
Analysis of Factors Affecting Maize Produstion in Southeast Aceh Regency. Kabupaten Southeast Aceh Selected for this study on the grounds that the district is corn production areas in the province. Samples selected district Subdistrict Lawe Alas, Badr and Bukit Pine as corn production centers firs, second and third in Southeast Aceh Regency. The population in this study was 120 randomly selected maize farmers spread over three district of samples and 9 samples of selected villages in the study area. The model used data analysis aided by SPSS software version 17 in data processing. The results of this study are : obtained value of R2 (coefficient of determination) = 0.992, F value obtained = 2831.918 (synchronously very significant influence), t test (test separately the effect of independent variables on the dependent variable) can be concluded : land area (X1) very significant effect on maize (Y) and labor (X2) / fertilizer (X4) / pesticide (X5) Significantly affects corn production (Y). while seed (X3) does not significantly affect maize production (Y). Keywords : Corn, Production, Land Area, Labor, Seeds, Fertilizers, Pesticides